Differential transcriptome analysis supports Rhodnius montenegrensis and Rhodnius robustus (Hemiptera, Reduviidae, Triatominae) as distinct species - De Carvalho, Danila Blanco [UNESP]; Congrains, Carlos; Chahad-Ehlers, Samira; Pinotti, Heloisa [UNESP]; De Brito, Reinaldo Alves; Da Rosa, Joaõ Aristeu [UNESP] (Public Library of Science (PLoS), 2017)
Chagas disease is one of the main parasitic diseases found in Latin America and it is estimated that between six and seven million people are infected worldwide. Its etiologic agent, the protozoan Trypanosoma cruzi, is transmitted by triatomines, some of which from the genus Rhodnius. Twenty species are currently recognized in this genus, including some closely related species with low levels of morphological differentiation, such as Rhodnius montenegrensis and Rhodnius robustus. In order to investigate genetic differences between these two species, we generated large-scale RNA-sequencing data (consisting of four RNA-seq libraries) from the heads and salivary glands of males of R. montenegrensis and R. robustus. Transcriptome assemblies produced for each species resulted in 64,952 contigs for R. montenegrensis and 70,894 contigs for R. robustus, with N50 of approximately 2,100 for both species. SNP calling based on the more complete R. robustus assembly revealed 3,055 fixed interspecific differences and 216 transcripts with high levels of divergence which contained only fixed differences between the two species. A gene ontology enrichment analysis revealed that these highly differentiated transcripts were enriched for eight GO terms related to AP-2 adaptor complex, as well as other interesting genes that could be involved in their differentiation. The results show that R. montenegrensis and R. robustus have a substantial quantity of fixed interspecific polymorphisms, which suggests a high degree of genetic divergence between the two species and likely corroborates the species status of R. montenegrensis.